2010
DOI: 10.1103/physrevlett.105.216804
|View full text |Cite
|
Sign up to set email alerts
|

Anyon Condensation and Continuous Topological Phase Transitions in Non-Abelian Fractional Quantum Hall States

Abstract: We find a series of possible continuous quantum phase transitions between fractional quantum Hall (FQH) states at the same filling fraction in two-component quantum Hall systems. These can be driven by tuning the interlayer tunneling and/or interlayer repulsion. One side of the transition is the Halperin (p, p, p − 3) Abelian two-component state while the other side is the non-Abelian Z4 parafermion (Read-Rezayi) state. We predict that the transition is a continuous transition in the 3D Ising class. The critic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 32 publications
2
99
0
Order By: Relevance
“…As the external field can be turned on and off, the synthetic dislocations can be produced and moved around physically. On the other hand, the external field (or coupling) also drives intrinsic anyon condensation 10,16 along the branch-cut line, which demonstrates our designing principle of synthetic dislocations by anyon condensation. This makes synthetic dislocations more general than the lattice dislocations, since we can choose to condense different types of anyons, which in turn generates different kinds of topological degeneracies, associated to different synthetic dislocations with different projective non-Abelian statistics.…”
Section: Introductionmentioning
confidence: 99%
“…As the external field can be turned on and off, the synthetic dislocations can be produced and moved around physically. On the other hand, the external field (or coupling) also drives intrinsic anyon condensation 10,16 along the branch-cut line, which demonstrates our designing principle of synthetic dislocations by anyon condensation. This makes synthetic dislocations more general than the lattice dislocations, since we can choose to condense different types of anyons, which in turn generates different kinds of topological degeneracies, associated to different synthetic dislocations with different projective non-Abelian statistics.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the interlayer repulsion V inter is smaller than the intralayer repulsion V intra . When V inter % V intra , a quantum phase transition to a different many-body state is generally expected to occur [45][46][47]. In a flat band with Chern number C 1 ¼ 2, the different layers are separated by a lattice translation.…”
Section: Wannier-function Description Of Chern Insulatorsmentioning
confidence: 99%
“…In our study of bilayer quantum Hall phase transitions in Ref. 21, it was suggested that this transition, in the presence of the δL term, may be dual to a 3D Ising transition. In those cases, one starts from an Abelian bilayer FQH phase and obtains the non-Abelian orbifold FQH states by tuning the interlayer tunneling and/or interlayer repulsion.…”
Section: A Transition To Twisted Zn Topological Phasesmentioning
confidence: 99%
“…This formulation of the effective field theory allowed us to show that there is a continuous phase transition, in the 3D Ising universality class, between the Z 4 parafermion states and the Abelian (k, k, k − 3) states in bilayer quantum Hall systems. 21 Subsequently, it was found that for more general values of the coupling constants, k, l = 0, the U (1) × U (1) ⋊ Z 2 CS theory describes a series of non-Abelian FQH states -the orbifold FQH states. 22 The Z 4 parafermion FQH states are then a special case of these more general orbifold FQH states, which are separated from the (k, k, k−l) states by a continuous 3D Ising phase transition.…”
mentioning
confidence: 99%